Metode mellom forskning og læring Refleksjon og praksis - Hognestad, Karin; Bøe, Marit; Frers, Lars (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
This book employs a range of approaches to answer the question of how to use qualitative methods in a way that opens for reflections on the development and the study of professional practice in teacher education. Knowledge is displayed in action. Since this is also true for professional practice, the methods used by the contributors to this book are oriented towards practical action in the field of education, from early childhood education to higher education. Development, reflection, learning and research are tightly interwoven, as is displayed by researchers, teachers, and students when they participate and reflect upon different kinds of learning processes. The book is dealt in three parts, all of which examine reflection in relation to the fundamental terms method, research, and learning. The first part discusses method in a field of tension between everyday practice, research, and learning. The second part focuses on reflection in different areas of university students practicum during their education. The third and final part highlights the different ways in which processes of reflection are relevant in the context of classroom studies. All contributors to Method between research and learning - Reflection in practice are members of the interdisciplinary research group Qualitative methods in professional practice at University College of Southeast Norway.